1988
DOI: 10.1351/pac198860111635
|View full text |Cite
|
Sign up to set email alerts
|

Captodative substituent effects in radical chemistry

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…(34) Radical thiol−ene polymerizations limited by chain transfer, such as the thiol−allyl ether polymerization, generally involve a relatively stable radical that is slow to abstract a thiol hydrogen. Sulfide substituents are believed to have a stabilizing effect on neighboring radicals, 35,36 which may explain the rate-limiting chain transfer step in the thiol−yne polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…(34) Radical thiol−ene polymerizations limited by chain transfer, such as the thiol−allyl ether polymerization, generally involve a relatively stable radical that is slow to abstract a thiol hydrogen. Sulfide substituents are believed to have a stabilizing effect on neighboring radicals, 35,36 which may explain the rate-limiting chain transfer step in the thiol−yne polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies addressed the change of BDEs of the C α H bond in toluene upon the presence of para substituents . It was found that the benzyl radical is stabilized upon introduction of a substituent group, irrespective of whether the Z group is an electron donor or acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…Free‐radical processes are known to be sensitive to both radical and polar effects (28, 29), which could explain the observations. One argument against a HAT process is the fact that the calculated bond dissociation energies in substituted acetophenone oximes were reported to be relatively independent of the substituent (30, 31).…”
Section: Introductionmentioning
confidence: 86%